We have two equations here:

4y = 4x + 4 ...(1) => y = (4x + 4)/4

= x + 1 ... (1a)

7y = 9x - 7 ... (2)

Substitute (1a) to (2)

7(x+1) = 9x -7

7x + 7 = 9x - 7

7x - 9 x = -7 - 7

- 2x = -14

x= -14/-2 = 7

Substitute x = 7 to (1a)

y = x + 1

= 7 + 1

= 8

(x, y) => (7,8)

We'll solve the system of equations using substitution method.

We'll isolate y to the left side, such as the first equation give:

y = (4x+4)/4

y = 4(x+1)/4

y = x + 1 (1)

We'll isolate y to the left side, such as the second equation gives:

y = (9x-7)/7 (2)

We'll equate (1) and (2):

x + 1 = (9x-7)/7

We'll multiply by 7 both sides:

7(x+1) = 9x - 7

We'll remove the brackets:

7x + 7 = 9x - 7

We'll move the terms in x to the left side:

7x - 9x = -7 - 7

-2x = -14

x = 7

From (1) => y = x + 1 <=> y = 7 + 1 = 8

**The solution of the system is represented by the pair (7 ; 8).**